Tolerance Training with Adolescents in a Residential Juvenile Facility. Issue 4 (July 2021) - O'Rourke, Soracha; Richling, Sarah; Brogan, Kristen; McDougale, Cassidy; Rapp, John T.
For individuals receiving treatment in residential juvenile facilities, the inability to tolerate typical but unpleasant stimulus events may manifest in aggressive behavior toward staff or other residents. Such behaviors can lead to loss of privileges, interfere with other treatments, and contribute to negative staff-student relationships. As a procedure, tolerance training (TT) involves systematically increasing the duration of exposure to an undesired stimulus event or situation. The current study evaluated the effects of a procedure to increase tolerance of aversive situations for four adolescents who were receiving treatment for sexual offenses in a residential detention facility. Results from single-subject experimental designs indicate that TT increased all four adolescents' ability to tolerate a non-preferred stimulus event. We briefly discuss the clinical implications of the use of behavior-analytic procedures to improve skill sets for adolescents in residential treatment facilities.